EFFORTS TO SURVIVE IN SCOTT NEUSTADTER’S AND MICHAEL H. WEBER’S MOVIE SCRIPT THE FAULT IN OUR STARS - Fakhira Fakhira; Zulfan Sahri (JOURNAL OF LANGUAGE, 2021)
This paper deals with the Effort to Survive in Scott Neustadter’s and Michael H. Weber’s movie script The Fault In Our Stars, and it refers to two topics of discussion i.e. pleasing herself and doing medication ; the protagonist’s effort to stay alive is due to suffering from stage 4  thyroid cancer. In analyzing the two topics, the descriptive qualitative method is taken as most appropriate method  to process the data. The analysis indicates that the protagonist encouragingly makes some efforts for her healthy treatments as to please herself involving meeting her lover, going for a picnic, and meeting her favorite author; as to do medication by doing some therapies and joining support group. The results shows that the protagonist has attempted so hard to survive by doing things for her recovery; her cancer disease needs to have psychological treatment that can please herself and by doing medical treatment, medical therapies to cure a rare form of cancer. All of these are the protagonist’s efforts to live her life longer.